On the vesica of Eucosmini and Grapholitini (Insecta: Lepidoptera: Tortricidae) - Zlatkov, Boyan (Zootaxa, 2016)
Eucosmini and Grapholitini are highly specialised and closely related tribes of the subfamily Olethreutinae of the family Tortricidae. Previous studies have shown that there is considerable similarity in the general shape of the everted vesica and structure of cornuti in these two tribes. In this study the possible function of the vesica during copulation is discussed based on everted vesicae of intact specimens treated with dichlorvos, a compound that causes eversion of the vesica and formation of the spermatophore. A comparison between chemically and mechanically everted vesicae showed that the vesica consists of two functionally different parts: an eversible and a non-eversible. Clear distinction in the position and function of deciduous and non-deciduous cornuti was observed; non-deciduous cornuti are attached to the eversible part of the vesical and the deciduous cornuti to the non-eversible part. The mechanism of detachment of deciduous cornuti was revealed. Some peculiarities of the possible interaction between male and female genitalia are discussed.